PHILOSOPHICAL PERSPECTIVE OF ISLAM IN JAVANESE CULTURE: A STUDY OF FOSSIL ROCKS OF APAK 'BERINGIN' - Teguh (European journal for philosophy of religion, 2023)
This study investigated the perspective of Javanese Islamic philosophy on the Apak 'Beringin' rock fossil and its impact on the level of spirituality and community behavior, using a qualitative descriptive method with a phenomenological approach. Data analysis techniques were carried out using observation, interviews, and literature studies focusing on textual and contextual interpretations of the 'Beringin' Apak Fossil Rock. The main data sources came from the book of philosophy otak-athik gathuk (Javanese Islamic philosophical thought) by Damardjati Supadjar and the book of commentary as-Sulami by Imam Abu Abd. Muhammad bin Husayn as-Sulami. The findings revealed that in Javanese Islamic philosophy, the symbolization of the universe depicted in the form of fossilized rocks aimed to train the soul in understanding the origin and purpose of everything in the universe or known as 'sangkan paraning damadi'. This is a manifestation of the Javanese Muslim community's way of knowing God or what is known as divine awareness ‘ilahiyah’. In the rock fossils that have been found, there are words Allah and Muhammad considered by the Javanese as a natural permit that is only obtained by people who reach certain maqam. The conclusion is that based on the elaboration of the meaning of the natural text which is symbolized in the form of the 'Beringin' Fossil rock, it is a reflection of oneself to always be close to Allah SWT.